Induction of physical paramorphogenesis in Aspergillus sp - Contato, Ivonete Marcanti; Corso, Carlos Renato [UNESP]; De Oliveira, José Eduardo [UNESP] (My University, 1997)
A simple and easily reproducible method to obtain little fungical pellets from mycelial fractionization, completely under control with respect to development, size and homogeneity without genetic compromise, is described. The method has been successully employed with Aspergillus niger and also showed similar results with Aspergillus oryzae.
Keywords: A. oryzae; Adsorption; Aspergillus niger; Filamentous fungi; Paramorphogenesis